Green Marketing Practices Prevailing In Hotel Industry - MISHRA, DR. A.B.; SAHU, DR. TRIPTI; RANJAN, DR. NITIN; VARMA, PROF. ANIL (The journal of contemporary issues in business and government, 2021)
Hospitality industry has always the forerunner in its responsibility towards environment and has been recognized for greening efforts. It gives an added advantage in attracting global traveler and has been an appealing feature of this industry. The industry has taken green efforts in planning and design of green products, creating and delivering green services, distributed and priced the products and services without harming environment, created environment friendly infrastructure and reduced carbon emissions. This paper is an empirical study of green marketing practices the hospitality has adopted over a period of time and has explored the way green practices are communicated to consumers. The innovative techniques of emotional message and visual communication about environmental characteristics of hotels are investigated in the study.